2018
DOI: 10.5740/jaoacint.18-0044
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Nanodiamonds in Biomedical Applications

Abstract: Nanoparticles have an extended surface and a large surface area, which is the ratio of the size of the surface area to the volume. A functionalized surface can give rise to more modifications and therefore allows this nanomaterial to have new properties. Fluorescent molecules contain fluorophore, which is capable of being excited via the absorption of light energy at a specific wavelength and subsequently emitting radiation energy of a longer wavelength. A chemically modified surface of nanodiamond (ND; by car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Nanodiamonds receive special attention within the range of nanocarbon materials due to their outstanding physical and chemical features [5,6]. This versatile material exhibits low cytotoxicity at the cellular level [7,8] and is considered the most biocompatible of all carbon-containing derivatives [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Nanodiamonds receive special attention within the range of nanocarbon materials due to their outstanding physical and chemical features [5,6]. This versatile material exhibits low cytotoxicity at the cellular level [7,8] and is considered the most biocompatible of all carbon-containing derivatives [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For biological applications, the excellent biocompatibility of fluorescent nanodiamonds is also crucial [9]. In several previous studies, FNDs are introduced in mammalian cells and have shown no negative effects [10][11][12]. From these studies, it is known that mammalian cells passively take up FNDs in different ways depending on the cell type and exact conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-based nanomaterials are a very differentiated group covering allotropic forms with a distinct crystallographic structure. Particularly interesting materials are powders and nanopowders, because they have a developed surface with the possibility of chemical and plasma-chemical functionalization of their surfaces [1][2][3][4][5]. Finally, it is possible to obtain films and laminates with modified carbon nanostructures that have controlled surface activity for packaging fat-containing products [2][3][4][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly interesting materials are powders and nanopowders, because they have a developed surface with the possibility of chemical and plasma-chemical functionalization of their surfaces [1][2][3][4][5]. Finally, it is possible to obtain films and laminates with modified carbon nanostructures that have controlled surface activity for packaging fat-containing products [2][3][4][6][7][8]. Different allotropic forms of carbon (diamond, graphite, carbine) and various forms of carbon (graphene, nanotubes, fullerenes) influence the colonization and biological activity of foodborne pathogens on chicken embryo development, including angiogenesis.…”
Section: Introductionmentioning
confidence: 99%